FEATURES OF TROPHISM OF BONE TISSUE AFTER THE INSTALLATION OF DENTAL IMPLANTS - A. V. Ivaschenko; A. E. Yablokov; I. I. Markov; V. A. Monakov; A. M. Nesterov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. The most important condition for a successful result of dental implantation is high-quality osseointegration of dental implants. In the literature, the issue of the quality of osseointegration is widely covered, which directly depends on the primary stability of dental implants. In the area of bone tissue remodeling, surrounding the installed dental implants, there are permanent processes of bone resorption and its restoration [1, 2]. The aim is to reveal the reactivity of alkaline phosphatase and osteocalcin in the biological fluid (saliva) in patients after dental implants. Materials and methods. The collection and analysis of clinical material was carried out on the basis of the Clinics of the Samara State Medical University of the Ministry of Health of Russia. Dental implantation surgery was performed in 184 patients aged 32 to 65 years. The gender ratio was 2:3 (40 men and 60 women). The teeth were lost due to poor oral hygiene and  caries complications. Results and discussion. At the time of admission of patients to the department of the Department of Prosthetic Dentistry of the Clinics of the Samara State Medical University of the Ministry of Health of Russia, the bulk  of the patients had a low hygienic status. The OHI-S index averaged 2.74 ±  0.33 conventional units. (control – 0.50 ± 0.07 c.u.). In order to reduce the negative influence of microorganisms in the supra- and subgingival dental  deposits, all patients underwent professional oral hygiene, as well as  antimicrobial therapy. At the time of installation of dental implants, the average OHI-S and Müllemann-Cowell index was 0.72 ± 0.06 and 0.57 ± 0.06 conventional units, respectively. Conclusions. 1. The increase in the titer of alkaline phosphatase and  osteocalcin during dental implantation is not statistically significant. 2. TCRF  in the oral fluid (saliva) exhibits maximum activity by the 14th day, exceeding  the initial three times. This indicator remains at an increased level  in the period up to six months from the beginning of the operation. 3. Revealing the values of the TRKF titer after the operation of dental  implantation is advisable to use as an assessment of the state of trophic  processes occurring in the bone tissue.